Junctophilin-2 gene therapy rescues heart failure by normalizing RyR2-mediated Ca2+ release - Reynolds, Julia O.; Doroudgar, Shirin (International journal of cardiology, 2016)
Junctophilin-2 (JPH2) is the primary structural protein for the coupling of transverse (T)-tubule associated cardiac L-type Ca channels and type-2 ryanodine receptors on the sarcoplasmic reticulum within junctional membrane complexes (JMCs) in cardiomyocytes. Effective signaling between these channels ensures adequate Ca-induced Ca release required for normal cardiac contractility. Disruption of JMC subcellular domains, a common feature of failing hearts, has been attributed to JPH2 downregulation. Here, we tested the hypothesis that adeno-associated virus type 9 (AAV9) mediated overexpression of JPH2 could halt the development of heart failure in a mouse model of transverse aortic constriction (TAC). Following TAC, a progressive decrease in ejection fraction was paralleled by a progressive decrease of cardiac JPH2 levels. AAV9-mediated expression of JPH2 rescued cardiac contractility in mice subjected to TAC. AAV9-JPH2 also preserved T-tubule structure. Moreover, the Ca2+ spark frequency was reduced and the Ca2+ transient amplitude was increased in AAV9-JPH2 mice following TAC, consistent with JPH2-mediated normalization of SR Ca2+ handling. This study demonstrates that AAV9-mediated JPH2 gene therapy maintained cardiac function in mice with early stage heart failure. Moreover, restoration of JPH2 levels prevented loss of T-tubules and suppressed abnormal SR Ca2+ leak associated with contractile failure following TAC. These findings suggest that targeting JPH2 might be an attractive therapeutic approach for treating pathological cardiac remodeling during heart failure.
Gesehen am 06.09.2017